Relative thermal stability of Thiolate- and Selenolate-bonded aromatic monolayers on the Au(111) substrate - Ossowski, Jakub; Zharnikov, Michael (The journal of physical chemistry. C, Energy, materials, and catalysis, 2017)
The thermal stability of self-assembled monolayers (SAMs) is of fundamental importance for the majority of their applications. It strongly depends on the type of chemical group used for bonding the molecules forming the SAMs to the selected substrate. Here, we compare the impact of using S and Se bonding groups on the thermal stability of aromatic model SAMs based on naphthalene, containing a polar substituent, and formed on a Au(111) substrate.
Gesehen am 09.04.2018